25=n-(-6)

Simple and best practice solution for 25=n-(-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25=n-(-6) equation:



25=n-(-6)
We move all terms to the left:
25-(n-(-6))=0
We calculate terms in parentheses: -(n-(-6)), so:
n-(-6)
We add all the numbers together, and all the variables
n+6
Back to the equation:
-(n+6)
We get rid of parentheses
-n-6+25=0
We add all the numbers together, and all the variables
-1n+19=0
We move all terms containing n to the left, all other terms to the right
-n=-19
n=-19/-1
n=+19

See similar equations:

| −10t–(t+5)=28 | | v-44=44 | | (2x+18)+(x+15)=180 | | x,4x-10=18 | | 6x+36=4x-16 | | -x+4=-7x-16 | | -10=6x-2x+6 | | 12=x+6-3x | | 33/4w=30 | | 2.3x+24.8=6.5+3.8 | | 18.75+(3.25x)=35 | | 4(29+2)=8(2-3a) | | 2(3y-7)+2y=6y+12 | | -1+p=-14 | | 6=k10 | | 25+y=30 | | 2n+15=-13 | | 12a-1=35 | | x2+3xx=7 | | 17=6y-3y+2 | | 0.5(3-5x)=8-(5x+4) | | 1.2x-12=-3 | | =v+815 | | (y-20)+9(14)-1=180 | | 19x-11=28 | | 25x-6=5(5x+3) | | 36=3x+13.5 | | 5x-12=-2x+16 | | (y+3)^2=3(2y+6) | | 5x-x=-10 | | (y-20)+(9×14-1)=180 | | (4x-3)^2+7=88 |

Equations solver categories